Rancangan Bangun Sistem Informasi Jasa Event Broadcasting Berbasis Website Pada Vendor Haimatt Project - Oki Tiara Dewi; Sofyan Mufti Prasetiyo (CV. Multi Kreasi Media, 2022)
This final project research is in the form of a website-based information system design for event broadcasting services at the Haimatt Project, which at the time the research was carried out event broadcasting services were still using manual methods for data storage processes, order processing and orders by clients. The method used by the author is a waterfall system development model (Sommervile, 2011). The stages of the waterfall system consist of needs analysis, application design, program process, system testing and system maintenance. The design of UML (Unified Modeling Language) which consists of several techniques, Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. The database design used is Entity Relationship Diagram (ERD), Transformation of ERD to LRS and Logical Record Structure (LRS). The purpose of this research is to design an information system for broadcasting event services that can facilitate both employees and customers in conducting transactions or processing data on the Haimatt Project.